The dynamics of persuasion : communication and attitudes in the twenty-first century - Perloff, Richard M. (Routledge communication series, 2023)
"The eighth edition of The Dynamics of Persuasion again guides readers in understanding the power and limits of persuasion in contemporary society. This edition continues its accessible and detailed illustration of the theoretical underpinnings of persuasive communication through contemporary and relevant examples of persuasion in action. It features coverage of new scholarship on misinformation, health communication, and persuasion effects, including careful attention to persuasion's role in the Covid-19 pandemic. Important issues such as racial injustice, climate change, and barriers to persuading the politically and psychologically polarized also receive a fresh examination. The book brings together classic terms and approaches from earlier editions with new global developments to help readers adopt a more thoughtful perspective on persuasion. The eighth edition is an essential resource for courses in persuasion at the undergraduate and graduate levels within communication studies, psychology, and business programs. Online resources also accompany the text: an Instructor Manual that contains sample syllabi, key terms, chapter outlines, sample discussion questions, and links to relevant news articles and other online resources such as videos; Lecture Slides; and a Testbank. Please visit: www.routledge.com/9781032268187"